Making love with scripture : why the Bible doesn't mean how you think it means - Myers, Jacob D. (Minneapolis : Fortress Press, 2015)
Nothing has been more contentious in the history of Christianity than the meaning of the Bible, and that debate continues today. Arguments over scripture have divided denominations, churches, and families, and these squabbles have led many to abandon the faith altogether. Jacob D. Myers, a rising young scholar, has a solution to the problem with Scripture. The instability of the Bible's meaning, he argues, is not a weakness but a strength, and it can benefit conservatives and liberals alike. In a conversational style peppered with pop culture references, Myers provides a variety of tools for readers of the Bible, helping the experienced and inexperienced alike appreciate the sacred text in new ways. Finally, he proposes the intriguing alternative of an "erotic" interpretation, one that makes love with the Bible and opens new vistas of understanding.
Introduction: Does the dude really abide?: making theological meaning -- Shake 'n bake: reading scripture with Ricky Bobby -- Part I. Fifty shades of grey (matter): liberating God's liberating Word -- How to get away with murder: the death of the author -- 99 problems but the text ain't one: cultural interpretations of scripture -- Sméagol knows the way: liberation theologies of scripture -- Part II. Oppa Gangnam style: the Bible as rave -- Beware the Kragle: the world of deconstruction -- May the odds be ever in your favor: the Hunger Games of (biblical) interpretation -- Don't win the game, change it: radical theologies of scripture -- Part III. This is how we do it: reading the Bible today -- Selflessness and bravery aren't all that different: the self before the wor(l)d -- What does the fox say?: listening to the wor(l)d -- You can't handle the truth: the saturated wor(l)d -- Conclusion: Why Harry Potter always beats Voldemort: the power of love.
Includes bibliographical references.
Keywords: Bible -- Hermeneutics; Love -- Religious aspects -- Christianity; Theology, Doctrinal -- Popular works